2020
DOI: 10.7554/elife.63997
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative glycoproteomics reveals cellular substrate selectivity of the ER protein quality control sensors UGGT1 and UGGT2

Abstract: UDP-glucose:glycoprotein glucosyltransferase (UGGT) 1 and 2 are central hubs in the chaperone network of the endoplasmic reticulum (ER), acting as gatekeepers to the early secretory pathway, yet little is known about their cellular clients. These two quality control sensors control lectin chaperone binding and glycoprotein egress from the ER. A quantitative glycoproteomics strategy was deployed to identify cellular substrates of the UGGTs at endogenous levels in CRISPR-edited HEK293 cells. The 71 UGGT substrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 81 publications
0
38
0
Order By: Relevance
“…KEGG enrichment analysis of the differentially expressed proteins showed that the downregulated proteins UGGT1, HSPA5, HSPA8, and HSP90AA1 are enriched in protein processing in ER, the PI3K–AKT signaling pathway, RNA transport, and the estrogen signaling pathway in Lec1 cells, and in regulating the actin cytoskeleton via focal adhesion molecules in Lec4 cells ( Figure 3 B). UGGT1 is a carbohydrate-dependent chaperone which facilitates proper folding and maturation of the cellular N-glycoproteome [ 84 ]. The downregulated expression of heat shock proteins HSP90AA1, HSPA5, and HSPA8 was involved in apoptosis-related protein, antigen presentation, and the estrogen signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG enrichment analysis of the differentially expressed proteins showed that the downregulated proteins UGGT1, HSPA5, HSPA8, and HSP90AA1 are enriched in protein processing in ER, the PI3K–AKT signaling pathway, RNA transport, and the estrogen signaling pathway in Lec1 cells, and in regulating the actin cytoskeleton via focal adhesion molecules in Lec4 cells ( Figure 3 B). UGGT1 is a carbohydrate-dependent chaperone which facilitates proper folding and maturation of the cellular N-glycoproteome [ 84 ]. The downregulated expression of heat shock proteins HSP90AA1, HSPA5, and HSPA8 was involved in apoptosis-related protein, antigen presentation, and the estrogen signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Folding and processing of native polypeptides, the primary function of the Endoplasmic Reticulum (ER), are mediated by a cadre of ER-resident protein chaperones. ER dysfunction leads to an increase in misfolded proteins in the ER lumen, a condition known as ER stress [ 1 ]. ER stress activates ER-transmembrane proteins, including Protein RNA-like Endoplasmic Reticulum Kinase (PERK), Inositol-Regulated Enzyme 1-alpha (IRE1α), and Activating-Transcription Factor 6-α (ATF6α).…”
Section: Introductionmentioning
confidence: 99%
“…Folding and processing of native polypeptides, the primary function of the Endoplasmic Reticulum (ER), are mediated by a cadre of ER-resident protein chaperones. ER dysfunction leads to an increase in misfolded proteins in the ER lumen, a condition known as ER stress (Adams et al 2020). ER stress activates ER-transmembrane proteins, including Protein RNA-like Endoplasmic Reticulum Kinase (PERK), Inositol-Regulated Enzyme 1-alpha (IRE1α), and Activating-Transcription Factor 6-α (ATF6α).…”
Section: Introductionmentioning
confidence: 99%